The Influence of Self-Compassion and Psychological Well-Being in Quarter-Life Crisis Among Students - Merdika, Natasya; Hartanti, Jahju; Listyowati, Anies (Universitas Muhammadiyah Metro, 2025)
The phenomenon of the quarter-life crisis frequently occurs among individuals aged 20 to 30 years, a period known as emerging adulthood. This prolonged crisis phase is primarily attributed to low levels of well-being, which are influenced by self-compassion—a factor with both preventive and promotive potential. This study aims to examine how self-compassion affects the psychological well-being of emerging adults experiencing a quarter-life crisis in Surabaya. Employing a quantitative research approach, the study utilizes a closed-ended questionnaire for data collection. The findings confirm that self-compassion has a positive impact on psychological well-being and serves as a protective factor in coping with the quarter-life crisis. By recognizing difficulties as a natural part of life, students with higher self-compassion are better able to accept themselves, regulate their emotions effectively, and develop more stable psychological well-being.